Oceanic Feedback to the Atmosphere for Anomalous SST Events Peaking in Early Winter in the Northeast Pacific - Xi Hu; Jian Shi; Xiaohui Ma; Yanjing Tang; Zhao Jing (Geophysical Research Letters)
Abstract In the past decade, large‐scale and persistent warm sea surface temperature anomalies (SSTA) occurred frequently in the mid‐latitude Northeast Pacific (NEP), offering a valuable opportunity to further illuminate the oceanic feedback to the atmosphere, which has been a complex issue for mid‐latitude ocean‐atmosphere interaction. Previous studies reported that the prolonged warm SSTAs in the NEP are usually passively triggered by atmospheric high‐pressure anomalies. In this study, results show that the early winter positive SSTAs can actively reverse the high‐pressure anomalies into low‐pressure anomalies within the whole troposphere through diabatic heating and transient eddy vorticity forcing. However, when the positive SSTAs appear in mid‐winter, the atmospheric preconditioning of warm air temperature anomalies related to the high‐pressure anomalies prevents oceanic thermodynamic and dynamics feedback onto the atmosphere, which results in no reversal of the high‐pressure anomalies. Therefore, the atmospheric state is an important factor in initiating the mid‐latitude oceanic feedback to the atmosphere.